PENGEMBANGAN APLIKASI SELULER LINGKAR LENGAN ATAS IBU HAMIL BERBASIS ANDROID - M Aris Rizqi; Guswan Wiwaha; Dewi Marhaeni Diah Herawati (Poltekkes Kemenkes Bandung, 2021)
Chronic energy deficiency (CED) has a major impact on maternal health. Screening is carried out to prevent the risk of CED for the mother before and during pregnancy by measuring the upper arm circumference (MUAC). This study aims to explore, validate and analyze the sensitivity and specificity of the MUAC mobile application. his research is expected to help health cadres in measuring the MUAC of pregnant women. This study uses a mixed-method with a sequential exploratory strategy with a purposive sampling technique. Exploration was carried out on 3 nutritionists and 7 Posyandu cadres. Data collection was done using of in-depth interviews. The feasibility test was conducted on 5 informatics experts, 5 nutritionists and 30 Posyandu cadres using a questionnaire. Mobile apps sensitivity and specificity test LILA was performed on 37 pregnant women purposively and analyzed using Stata software. Mobile apps model exploration results MUAC for pregnant women consists of content, design, measurement techniques and accuracy. Expert test results and user tests show mobile apps MUAC pregnant women are valid and reliable. The results of the sensitivity test (91.2%) and specificity (33.3%). Mobile apps models MUAC for pregnant women was developed based on user needs. Mobile apps MUAC for pregnant women has very good sensitivity and poor specificity. Further research is required to conduct similar studies to obtain better sensitivity and specificity results.